Precocious Puberty and the Lin28/Let7 Pathway: The Therapeutic Effect of the Nourishing "Yin" and Purging "Fire" Traditional Chinese Medicine Mixture in a Rat Model. (26th June 2018) - He, Yuanyuan; Han, Xinghui; Sun, Wen; Yu, Jian; Tamadon, Amin
Abstract : The present study aims to investigate the effects of the nourishing "Yin" and purging "Fire" Traditional Chinese Medicine (TCM) herb mixture on precocious puberty and TCM may act through hypothalamic Lin28/let7 pathway expression in the precocious puberty model rats. Meanwhile, to confirm the relationship between Lin28/let7 pathway and puberty by overexpression Lin28a, in the first part of this study, female rats were randomly allocated into untreated controls, the precocious puberty (PP) model group, the PP control group, and the PP + TCM group. Rats on postnatal day 5 were injected danazol to establish the PP model. From days 15 to 35, the rats in the TCM group were given the TCM twice daily. Vaginal opening, sex-related hormones, and body and reproductive organ weights were measured, and the expressions of hypothalamic Lin28a and Lin28b mRNA and let7a and let7b miRNA were detected. In addition, in the second part, the effects of overexpression of Lin28a on the vaginal opening time were evaluated. In the two parts of the study, we found that, at the onset of puberty, a decrease in ovary weight, an increase in the serum levels of luteinizing hormone and progesterone, and increased expression levels of hypothalamic Lin28b mRNA were observed in the PP + TCM group compared to the PP model group. The vaginal opening time was significantly delayed upon overexpression of Lin28a . Above all, the mechanism by which the TCM treats precocious puberty is thus likely to be associated with inhibition of the hypothalamic Lin28/let7 signaling pathway and our findings provide in-depth insight into the relationship between the overexpression of Lin28a gene in the hypothalamus and the onset of puberty.